High-entropy metal oxide containing hybrid electrolyte for long-life Li-metal batteries. Issue 1 (17th November 2022) - Li, Mingsheng; Wang, Liqi; Shi, Yongzheng; Zhang, Jikai; Zhu, Qi; Shang, Jiaxiang; Li, Bin; Yang, Shubin
Abstract: Solid-state electrolytes are responsible for transporting lithium (Li) ions between electrodes in solid-state batteries and are essential for high-safety and high-energy Li-metal batteries. Developing novel solid-state electrolytes with high ionic conductivity and good interfacial contact is an urgent need. Here, to this end, a solid-state hybrid electrolyte is developed by mixing high-entropy Li-containing metal oxide (Li x (Mg0.2 Co0.2 Ni0.2 Cu0.2 Zn0.2 )1− x O, HEOLi ) matrix and poly(ethylene oxide)–Li salt binder and casting on polytetrafluoroethylene (PTFE) substrate. By virtue of the low Li-ion migration energy barrier of the HEOLi (0.36 eV) and the strong interaction between the oxygen vacancies of the HEOLi and the Li salt anions, a biphasic transport of Li ions in both inorganic and polymeric phases of the hybrid electrolyte is achieved, yielding a high ionic conductivity of 3 × 10 −4 S cm −1 at 30°C. The Li/Li symmetric cells with the hybrid electrolyte show a low overpotential of 45 mV and a long cycle life of more than 2500 h. Furthermore, coupled with the LiFePO4 cathodes and metallic Li anodes, solid-state full cells with the hybrid electrolyte deliver a high capacity of 150 mAh g −1, stable cycle performance and high safety. Consequently, hybrid electrolytes based on high-entropy metal oxides have broad application prospects in solid-state electrochemical energy storage and are expected to achieve Li-metal batteries with high-safety, high-energy density and long life.